CLINICAL-ANAMNESTIC CHARACTERISTICS IN PATIENTS WITH BENIGN AND PRECANCEROUS PROCESSES IN UTERINE CERVIX WITH COMBINED UTERINE PATHOLOGY - Sha Sha; I. S. Sidorova; A. L. Unanyan; M. N. Zholobova; N. V. Vedernikiova; Yu. A. Rzyanina; A. E. Kadyrova (IRBIS LLC, 2016)
The objective of current research was to study clinical-anamnestic characteristics in women with benign and precancerous processes in uterine cervix with combined uterine pathology (myoma, adenomyosis, endometrial hyperplasia and benign processes in uterine cervix). The results demonstrate that changes in uterine cervixes are more frequent in patients with combined uterine diseases compared with patients with monopathology.